Implementation of the Malaysian Public Private Partnership (PPP) - Abdul Rashid, Khairuddin (IIUM Press, 2013)
This chapter aims to provide a basic understanding for the way in which PPP is being implemented in Malaysia. In particular, the chapter provides an overview on the Malaysia PPP and a review on the implementation of the Malaysia PPP focusing on the policies, modalities, process of procurement, contract arrangement and highlights some of the more pertinent issues and problems which have emerged. Admittedly, and by design, this chapter does not provide in-dept analysis of the practice, procedure and policies related to the Malaysian PPP.